2021
DOI: 10.4103/ua.ua_47_20
|View full text |Cite
|
Sign up to set email alerts
|

High rates of advanced prostate cancer in the Middle East

Abstract: Objectives: Prostate cancer incidence is increasing in the Middle East (ME); however, the data of stage at the diagnosis and treatment outcomes are lacking. In developed countries, the incidence of de novo metastatic prostate cancer ranges between 4% and 14%. We hypothesized that the rates of presentation with advanced disease are significantly higher in the ME based on clinical observation. This study aims to examine the stage at the presentation of patients with prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This is in line with findings from a recent publication which reported that a high percentage of men present with locally advanced and metastatic PC at diagnosis in the ME [ 22 ]. Additionally, a recent ME study, conducted at a large tertiary care centre that receives referrals for PC patients across the region, reported high proportions of patients diagnosed at stage III (Lebanon: 18%, Iraq: 25%, Syria: 33%) and IV (Lebanon: 19%, Iraq: 52%, Syria: 20%) [ 23 ]; it is of interest to note the variance in proportions by nationality – however, an important limitation of the study is that the vast majority of patients (71.4%) were Lebanese. The higher proportions of advanced PC stages reported in our study may partly be due to differences in the study populations, as the current study covered a broader range of populations across the ME.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings from a recent publication which reported that a high percentage of men present with locally advanced and metastatic PC at diagnosis in the ME [ 22 ]. Additionally, a recent ME study, conducted at a large tertiary care centre that receives referrals for PC patients across the region, reported high proportions of patients diagnosed at stage III (Lebanon: 18%, Iraq: 25%, Syria: 33%) and IV (Lebanon: 19%, Iraq: 52%, Syria: 20%) [ 23 ]; it is of interest to note the variance in proportions by nationality – however, an important limitation of the study is that the vast majority of patients (71.4%) were Lebanese. The higher proportions of advanced PC stages reported in our study may partly be due to differences in the study populations, as the current study covered a broader range of populations across the ME.…”
Section: Discussionmentioning
confidence: 99%
“…A confluence of unique circumstances and socio‐economic conditions within the Middle East could elucidate the paradox of higher prostate cancer mortality despite lower incidence rates in the region. One primary factor is the alarming rate of advanced prostate cancer diagnoses 7,9,18 . While the incidence of prostate cancer is increasing, data on the stage at diagnosis and treatment outcomes remain scarce, potentially leading to increased mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of factors contribute to this knowledge gap including limited resources for comprehensive cancer registries, cultural barriers to healthcare access, and varied healthcare systems across the countries in this region 6–8 . The available small institutional data suggest a consistent increase in the incidence of prostate cancer in this region over the last decade 9 . This increasing trend, combined with a rapidly aging population, has raised serious concerns about the future healthcare burden and costs that the region will have to bear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current therapies reside on radical prostatectomy or radiotherapy with good results regarding the 5-year survival rate for localized prostate cancer [ 3 ]. However, approximately one-third of patients developed metastatic disease and relapsed after local therapy, with bone as the most common site of metastasis, followed by lung and liver [ 4 7 ]. Standard treatments for advanced prostate cancer rely on androgen-deprivation therapies (ADT), paralleled by association with some recently discovered novel hormonal agents [ 8 ].…”
Section: Introductionmentioning
confidence: 99%